2011
DOI: 10.1631/jzus.b1101007
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of liposomal prostaglandin E1 on a porcine model of myocardial infarction reperfusion no-reflow

Abstract: Abstract:Objective: To evaluate whether liposomal prostaglandin E1 (lipo-PGE1) can decrease reperfusion no-reflow in a catheter-based porcine model of acute myocardial infarction (AMI). Methods: Twenty-two male Chinese mini-swines were randomized into three groups: six in a sham-operation group, and eight each in the control and lipo-PGE1 groups. The distal part of the left anterior descending coronary artery (LAD) in the latter two groups was completely occluded for 2 h, and then reperfused for 3 h. Lipo-PGE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…[ 25 ] Another experimental porcine model, of myocardial infarction reperfusion no-reflow, reported that Lipo-PGE1 is cardioprotective and decreases the no-reflow area while attenuating the inflammatory response. [ 10 ] This, in some ways, may explain the improvement of coronary microcirculation (cTFC and MBG) in our study. During 6-month follow-up, we found that patients receiving intravenous Lipo-PGE1 had less MACE, which was consistent with previously published studies.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…[ 25 ] Another experimental porcine model, of myocardial infarction reperfusion no-reflow, reported that Lipo-PGE1 is cardioprotective and decreases the no-reflow area while attenuating the inflammatory response. [ 10 ] This, in some ways, may explain the improvement of coronary microcirculation (cTFC and MBG) in our study. During 6-month follow-up, we found that patients receiving intravenous Lipo-PGE1 had less MACE, which was consistent with previously published studies.…”
Section: Discussionmentioning
confidence: 64%
“…However, experimental and clinical studies have demonstrated that myocardial impairment, known as reperfusion injury, may occur as a result of reperfusion. Recent reports have determined that the reperfusion injury is improved by administration of verapamil,[ 2 ] nicorandil,[ 3 4 5 ] adenosine,[ 6 7 ] nitroprusside,[ 8 ] anisodamine,[ 9 ] or prostaglandin E1 (PGE1)[ 10 11 ]. PGE1 reduces free radical production in stimulated human neutrophils and may attenuate reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…PGs2 are generally known as pro-inflammatory metabolites, whereas PGs1 possess anti-inflammatory effects [34]. Prostaglandins E1 (PGE1), which is a type of PGs1, could inhibit the proliferation of vascular smooth muscle cells and the adhesion of vascular cells, and the development of atherosclerosis [35,36]. Furthermore, DGLA is metabolized by the 15lipoxygenase into 15-(S)-hydroxy-8,11,13-eicosatrienoic acid (15-HETrE) [37] , which has been reported to reduce the development of DR because it inhibits the activity of vasoconstrictors and metabolites of AA including thromboxanes (TXs) and leukotrienes (LTs) [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that lipo-PGE1 can decrease coronary restenosis in a canine thrombolysis model 5 and reduce the incidence of periprocedural myocardial injury both in patients 6 and porcrine. 7 Lipo-PGE1 was also found to be effective for improving microcirculation. 8 The nanoliposome delivery system is also a popular method for targeted drug delivery, 9 and reviews have indicated that targeted nanoparticlemediated delivery of multifunctional drugs could be a promising approach to prevent or treat restenosis.…”
Section: Introductionmentioning
confidence: 95%